CGIAR Genebank Accelerator’s ‘submission of views on possible additional modalities of the multilateral mechanism’ - CGIAR Genebank Accelerator (2025)
This short submission from CGIAR’s Genebank Accelerator is in response to the call for submissions issued by the CBD Secretariat (SCBD/OES/DC/TS/CGA/KB/91971)